One dark throne - Blake, Kendare (Blake, Kendare. Three dark crowns ;, 2017)
The battle for Fennbirn has begun. The Quickening is behind them, and with the Ascension Year underway all bets are off. Katharine, once the weakest and feeblest of the triplets, is stronger than ever before. Arsinoe, after discovering the truth about her powers, must figure out how to make her secret talent work in her favor without anyone finding out. And Mirabella, once thought to be the strongest and the certain Queen Crowned, faces attacks like never before -- ones that put those around her in danger she can't seem to prevent.